ChemInform Abstract: Broensted Acid Catalyzed Intramolecular Benzylic Cyclizations of Alkylpyridines. Issue 27 (8th July 2014) - Lansakara, Ashabha I.; Farrell, Daniel P.; Pigge, F. Christopher
Abstract A series of hydroxyl lactams (II), (V), and (VIII) is prepared by benzylic cyclization of corresponding ketoamides using TfOH as a catalyst.